Constructional Ambiguity in Conversation - Ginzburg, Jonathan; Sag, Ivan A. (Proceedings of the Amsterdam Colloquium, 1999)
The paper considers the contents associated with clauses in conversational interaction, focussing particularly on the issue of how grammatical frameworks can accommodate uses such as intonation questions and reprise uses. We point out that the phenomena at issue are problematic for views of the syntax/ semantics interface such as radical lexicalism and syntactic modularity . We describe a grammatical system formulated within HPSG in which generalizations about phrasal types, characterized by means of constraints on both the syntactic and semantic components of the sign, are captured by means of · multiple inheritance hierarchies. We show how this system can accommodate the relevant phenomena.